Розробка модифікованих ітераційних алгоритмів для розв’язання задачі формування оптимальних варіантів розкладу виконання замовлень - Грибков, Сергій Віталійович; Сєдих, Ольга Леонідівна (My University, 2020)
У статті запропоновано математичну модель багатокритеріальної задачі формування виробничих завдань та оперативно-календарних планів з виробництва ковбасних і м’ясних виробів. Розроблено удосконалені ітераційні алгоритми на основі алгоритму сірих вовків та алгоритму мурашиної колонії для розв’язання задачі формування оптимальних варіантів розкладу виконання замовлень, що забезпечує при їх застосуванні реконфігурації планів за короткий час. In the article the mathematical model of multi-criterion problem of formation of industrial tasks and operative-calendarendar plans for performance of orders taking into account the basic features of activity of the enterprises on manufacture of sausage and meat products is offered. The mathematical model considers all nuances of activity of the food enterprise and process of planning of performance of orders: terms of storage of raw materials and finished goods; possibility of occurrence and necessity of processing of not confectionary production; features of performance of each separate order; features of use of the process equipment and so forth. To form a generalized target function, an additive convolution of criteria is used. The developed mathematical model allows to form the plan of performance of orders taking into account all operations of technological process at manufacturing of products. Advanced iteration algorithms based on the algorithm of grey wolves and an ant colony algorithm have been developed to solve the problem of forming optimal variants of the schedule of order execution, which provides for reconfiguration of plans in a short time when using them.
Keywords: математична модель; алгоритм зграї вовків; алгоритм мурашиної колонії; планування виконання замовлень; mathematical model; grey wolf algorithm; an ant colony algorithm; order scheduling; кафедра інформаційних технологій, штучного інтелекту і кібербезпеки